Pensioners Versus Employees in Romania: A Regional Study - Toma, Georgiana Cristina Rosu; Tuchilus, Gabriela (European Scientific Journal, ESJ, 2019)
Romania may become overwhelmed by its ageing population in the future. One of the worrying issues is the falling support rate, which shows the relationship between the working population who is paying taxes and the nonworking population, aged 65 years or over (the pensioners). This paper has a regional focus, this ratio and some of the factors influencing it (fertility rate, immigration or life expectancy) being studied in different regions of Romania between 1996 to 2017. Forecasts by 2060 highlight that pensioners-employees ratio will increase over time if no legislative reforms are designed to increase the social security budget (and implicitly the pension system). The findings indicate that an increase in fertility rate and immigration will contribute to better support of pensioners. Since many people migrate to developed countries, Romania is not attracting immigrants to improve its labor force. Hence, a measure to redress the demographic decline and support the pensioners could be the increase in the rate of fertility, which could be sustained by the initiation and implementation of pronatalist policies, the increase in the economic status of the family. Among the results, it is also highlighted that an increase in life expectancy will deter the support because the ageing population will grow. As a result, it is necessary to explore and to implement measures to balance the country’s social security budget having as target the old-age population.